Two bacteriophages which utilize a new Escherichia coli major outer membrane protein as part of their receptor. - Chai, T J (1978)
Escherichia coli strain JF694 contains a new major outer membrane protein which we have called protein E (J. Foulds, and T. Chai, J. Bacteriol. 133:1478-1483). Two new bacteriophages, TC45 and TC23, were isolated that require the presence of protein E in the outer membrane of host cells for growth. Both of these bacteriophages have a morphology similar to T-even bacteriophages but are distinct in properties such as plaque morphology, buoyant density, and burst size. Although strain JF694, containing protein E, adsorbs bacteriophage TC45 efficiently, cells killed with heat or chloroform are unable to inactivate this bacteriophage. Purified protein E either in the presence or absence of additional probable cofactors such as lipopolysaccharide was also unable to inactivate bacteriophage TC45. Both bacteriophages probably use protein E as at least part of their receptor but require, in addition, other outer membrane components or a specific orientation or organization of this protein in the outer membrane.